Strengthening the DPD RI Institution: Strengthening Regional Independence and the Bicameral System in Indonesia - Ginting, Fuad Putera Perdana; Tobing, Novan Andreas Lumban; Saragih, Anwar (Pencerah, 2025)
The purpose of this study is to explain the critical role of strengthening the institutional framework of the Regional Representative Council (DPD RI) in strengthening regional independence, particularly regarding the minimal authority of the DPD based on the constitution, namely proposing draft laws related to regional interests, and participating in discussions. This is, of course, not the basic authority of the parliamentary institution, but only a derivative of the authority of the DPR, which means the DPD is not a complete legislative institution because it does not have the authority to make final decisions in the political process. This research methodology is qualitative with descriptive analysis. The results of this study explain the institutional position of the DPD in the Indonesian constitutional system, the strengthening of the bicameral system, and the idea of amending the 1945 Constitution to strengthen the position of the DPD. Constitutional breakthroughs to improve the position of the DPD are essential because, since the DPD was established, there has been no breakthrough in its institutional function. Strengthening the function of the Regional Representative Council (DPD) through the fifth amendment to the 1945 Constitution is expected to optimize regional autonomy as an anchor of development and national integration. Therefore, it is also necessary to build the desire, togetherness, and will of stakeholders, such as political parties, the House of Representatives (DPR), the Regional Representative Council (DPD), academics, and the community, to realize the noble ideals of developing a more advanced, effective, and equitable Indonesia.